Integrating phase change materials in buildings for heating and cooling demand reduction – A global study - Andrew James Mettrick; Zhiwei Ma (Case Studies in Thermal Engineering)
This study aims to analyse the integration of Phase Change Materials (PCMs) in building envelopes globally, focusing on its ability to reduce the energy demand and its economic viability. The study conducted extensive simulations using the DesignBuilder software across 5684 locations globally and utilising artificial intelligence (AI) models to extend the simulation further to 73,515 locations, evaluating the impacts of PCM properties such as melting temperature (MT) and thickness. The main findings indicate that pronounced annual energy savings, 2500 to 3000 kWh, are observed in equatorial regions including northeast Brazil, central Africa, and the Malay Archipelago. Additionally, the optimal utilisation of increased PCM thickness is contingent upon selecting the correct MT and is most effective in regions with high average maximum temperatures, while the most common effective thickness is 20 mm. The study demonstrates that MT significantly affects energy savings, more than PCM thickness, highlighting the importance of selecting appropriate MT based on climatic conditions. The 25 °C MT is most effective within lower latitude range (−15°–30°), averaging 743.2 kWh greater savings than the 21 °C option. The 21 °C MT shows superior performance outside of this range, however the advantage is marginal as the average savings is 251.0 kWh. Economically, regions such as the USA, southern Europe (Spain and Italy), Brazil, and northern Australia show the best viability for PCM integration, aligning energy efficiency improvements with substantial economic returns. This comprehensive analysis suggests that tailored PCM integration strategies are essential for maximising energy savings and advancing sustainable building practices.